THE EFFECT OF MOTIVATION AND FAMILY SUPPORT FOR STUDENTS LEARNING ACHIEVEMENT LEVEL II PRODI - Faradilla Safitri; Feni Sasmita (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Learning achievement is thehuman levelof the studentsin accepting, rejecting, andassess theinformation obtainedin the learning process. The are many factors manyfactorsthat influence the successprocess in the learning, such as learning motivationandfamily support. Students' motivationbecome a low, so the quality of achievement will be low. Therefore, the quality ofthestudents'learning achievementneeds to be increased continuously in order forstudentsto havea strongmotivation to learn, so that thelearning performancecan be achievedoptimally. In theirfamilystudents needed the  support of their parentsin achievinglearning achievement, because the supportandattentionwilldetermine thestudentsreached a highacademic achievement. The purposeof thisstudywas to determine the"influence of motivation andfamily supporton student achievementlevelIIProdiD-III MidwiferySTIKesU'BudiyahBanda Aceh". This research isanalyticwith cross sectional approach. The populationinthis study were allsecondlevel studentsProdiD-III Midwifery, amounting to 73people. The sampling techniquetotal samplingwithcriteriaentiresecondlevel studentsare activein thefourth semester ofthe academic year2012/2013is73people. The research instrumentused questionnairesandtranscripts. This study was conductedon 20August to24 August, 2013. The results of this analysis study showed that there is influence of motivation on student achievement in grades P-Value = 0.000 (P <0.05) and no family support influences on student achievement in grades P-Value = 0.000 (P <0.05) . Based on the results of this study concluded that there was a significant relationship between motivation and family support on student achievement. Expected as input to the students and families that motivation and family support plays an important role in improving student achievement.Keywords: Motivation, family support, academic achievement